Molecular structure and infrared spectra of the monomeric 3-(methoxy)-1,2-benzisothiazole 1,1-dioxide (methyl pseudosaccharyl ether) - Kaczor, A. (2014)
The computational description of saccharin (1,2-benzisothiazol-3(2H)-one-1,1-dioxide) and its derivatives is difficult due to the presence of hypervalent S@O bonds in their structures. Therefore, in this investigation, the HF, DFT/B3LYP and MP2 methods were used to predict the geometry and the infrared spectrum of the saccharyl derivative 3-(methoxy)-1,2-benzisothiazole 1,1-dioxide (MBID). Their relative predictive capabilities were then evaluated by comparing the obtained results with experimentally available data, namely the newly obtained IR spectra of MBID isolated in low-temperature inert matrices. For each method, different basis sets [6-31++G(d,p), 6-31++G(3df,3pd), 6-311++G(d,p), 6-311++G(2df,2pd), 6-311++G(3df,3pd), aug-cc-pVDZ and aug-cc-pVTZ] were considered. The best overall agreement has been achieved at the B3LYP/6-311++G(3df,3pd) and B3LYP/6-31++G(3df,3pd) levels of theory, showing the adequacy of the B3LYP functional to describe the investigated properties in this type of compounds and stressing the relevance of including high-order polarization functions in the basis set. The chosen level of theory [B3LYP/6-311++G(3df,3pd)] was applied to analyze the vibrational spectra and the geometry of the title molecule. In agreement with the experiment, the CAOAC linkage in MBID is predicted by these calculations to exhibit considerably short (1.320A ˚ ) and long (1.442A ˚ ) (N@)CAO and (H3)CAO bonds, respectively, and a hybridization of the central oxygen atom close to sp2 (the CAOAC angle is predicted to be ca. 117 ). This CAOAC bonding pattern fits the well-known high reactivity of MBID upon thermal rearrangement, which has been shown to result in easy selective [1,30]-isomerization of the compound.